Investigating The Effect of Piezoelectric Material Type on Biomechanical Energy Harvesting Efficiency - Thashayani Sathasivam; Nur Hidayah Mansor (International Journal of Integrated Engineering, 2025)
This paper investigates the influence of piezoelectric material type on the performance of biomechanical energy harvesters, with a particular focus on footstep and finger-mouse-click energy-harvesting applications. A combination of design modelling and finite element analysis was employed to assess the energy conversion efficiency of various piezoelectric materials and their adaptability to dynamic forces generated by human motion. The findings indicate that PZT5H is the most efficient material for power generation in footstep harvesters, producing the highest power output of . Moreover, increasing the tip mass in the footstep model was found to enhance the voltage output further, reaching up to 3 . In contrast, PZT4 exhibited the highest energy harvesting efficiency from mouse-click motion, generating a power output of   . These findings offer in-depth insight into the capabilities of piezoelectric materials for integration into self-powered biomedical and wearable energy-harvesting applications.